Atypical Metastatic Disease in Thyroid from Pancreatic Neuroendocrine Tumor and its Response to [177Lu]Lu-DOTATATE Peptide Receptor Radionuclide Therapy (PRRT): A Promising Therapeutic Option for Somatostatin Receptor Expressing Unusual Metastatic Sites - Reddy, Mali Madhava; Parghane, Rahul Vithalrao; Basu, Sandip (World Journal of Nuclear Medicine, 2025)
There are no standardized treatment guidelines for this condition with atypical sites of metastatic disease in neuroendocrine tumors (NETs). We present a patient of pancreatic NET with liver metastasis and incidentally detected thyroid gland metastasis, a rare site of metastasis in the context of NETs. After two cycles of [177Lu]Lu-DOTATATE peptide receptor radionuclide therapy (PRRT), the metastatic thyroid lesion exhibited a remarkable response, as evidenced by neck ultrasonography and post-PRRT single photon emission computed tomography/computed tomography scan. This case upholds the fact that PRRT can demonstrate an excellent response at the atypical metastatic sites, thereby avoiding the necessity for surgical treatment and preventing morbidity associated with other therapeutic options.
Keywords: [177Lu]Lu-DOTATATE; peptide receptor radionuclide therapy (PRRT); neuroendocrine tumors (NET); thyroid metastasis; atypical metastatic sites